Recombinant Listeria ivanovii strain expressing listeriolysin O in place of ivanolysin O might be a potential antigen carrier for vaccine construction - Liang, Qian; Li, Ruidan; Liu, Sijing; Zhang, Yunwen; Tian, Sicheng; Ou, Qian; Chen, Zhaobin; Wang, Chuan (Frontiers in Microbiology, 2022)
Listeria monocytogenes (LM) is adapted for specialized intracellular parasitism, wherein it can survive and proliferate in host phagocytic cells, and directly infect neighboring cells. This mode of parasitism induces a highly efficient and specific T cell immune response in the host. Listeriolysin O (LLO) is the main virulence protein of LM. LLO helps LM escape from the lysosome. However, the pronounced pathogenicity of LM limits its practical application as a live bacterial vector. Listeria ivanovii (LI) also displays intracellular parasitic abilities, cell to cell transfer, and other LM properties, with an elevated biosafety relative to LM. We have confirmed that LI can be used as a viable bacterial vaccine vector. However, we have also observed in vivo that LI vector vaccine candidates survive in the immune organ (spleen) for a shorter time compared with the survival time of LM and elicit weaker immune responses compared with LM. Studies have confirmed that hemolysin correlates with some important biological properties of Listeria, including cell invasion, intracellular proliferation, and the ability to induce immune responses. We speculated that the weaker immunogenicity of LI compared to LM may be related to the function of ivanolysin O (ILO). Here, we established a hemolysin gene deletion strain, LIΔilo, and a modified strain, LIΔilo::hly, whose ilo was replaced by hly. The hemolysin-modified strain was attenuated; however, it led to significantly improved invasive and proliferative activities of antigen-presenting cells, including those of RAW 264.7 macrophages, compared with the effects of LI. Mice immunized twice with LIΔilo::hly showed higher cytokine levels and better challenge protection rates than LI-immunized mice. This is the first description in Listeria carrier vaccine research of the modification of LI hemolysin to obtain a better vaccine carrier than LI. The recombinant strain LIΔilo::hly showed good biosafety and immunogenicity, and thus appears to be a good vector strain for vaccine development.